Cancer in adolescents: Incidences and trends during 1995–2009 in Taiwan. Issue 1 (1st March 2016) - Hung, Giun-Yi; Chen, Chao-Chun; Horng, Jiun-Lin; Lin, Li-Yih
Highlights: Other epithelial neoplasms are the commonest adolescent cancer in Taiwan. Taiwan's adolescents have a low rate of Hodgkin's lymphoma. Rates of melanomas and NPCs were 1/10- and 4-times rates in Western countries. Male germ cell neoplasms had the most significant upward trend in incidence rates. Male hepatic tumors had the most significant declining trend in incidence rates. Abstract: This study aimed to describe cancer incidence rates and trends specifically for adolescents aged 15–19 years during 1995–2009 in Taiwan. The incidence counts and census data were obtained from the population-based Taiwan Cancer Registry. During the 15-year study period, 4122 adolescents were diagnosed with cancer. The overall incidence rate was 155.2 per million person-years. Other epithelial tumors were the most frequently diagnosed cancer group (23.7%), followed by leukemias (18.0%) and lymphomas (13.9%). When compared to rates in Western countries, a significantly low rate of lymphomas was found. Moreover, rates of the subtypes of melanomas and nasopharyngeal carcinomas being 1/10- and 4-times rates in Western countries were the most striking variations. During 1995–2009, the overall rate of adolescent cancer did not significantly change. However, the most significant upward and declining trends in incidence rates were found for male germ cell neoplasms (annual percent change, APC, 6.4%) and hepatic tumors (APC, -11.1%), respectively. Further investigation and enhancement of the public discourse of possible lifestyle and environmental risk factors associated with increasing trends of certain adolescent cancers should be carried out in Taiwan.